2019
DOI: 10.1111/nph.15797
|View full text |Cite
|
Sign up to set email alerts
|

Island woodiness underpins accelerated disparification in plant radiations

Abstract: Summary The evolution of secondary (insular) woodiness and the rapid disparification of plant growth forms associated with island radiations show intriguing parallels between oceanic islands and tropical alpine sky islands. However, the evolutionary significance of these phenomena remains poorly understood and the focus of debate. We explore the evolutionary dynamics of species diversification and trait disparification across evolutionary radiations in contrasting island systems compared with their nonisland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
55
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 119 publications
(199 reference statements)
4
55
2
Order By: Relevance
“…found higher diversification rates in the oceanic and sky‐island clades, as expected if ecological opportunities in island‐like environments act as an evolutionary stimulus (Stroud & Losos, ). Previous studies had found exceptionally high diversification rates in some island plant clades, including ones examined here, but Nürk et al . provide critical evidence that those rates represent acceleration of diversification in insular settings.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…found higher diversification rates in the oceanic and sky‐island clades, as expected if ecological opportunities in island‐like environments act as an evolutionary stimulus (Stroud & Losos, ). Previous studies had found exceptionally high diversification rates in some island plant clades, including ones examined here, but Nürk et al . provide critical evidence that those rates represent acceleration of diversification in insular settings.…”
supporting
confidence: 53%
“…Using model‐based tests for evolutionary rate differences between insular and noninsular clades, Nürk et al . found higher diversification rates in the oceanic and sky‐island clades, as expected if ecological opportunities in island‐like environments act as an evolutionary stimulus (Stroud & Losos, ).…”
mentioning
confidence: 66%
See 3 more Smart Citations